2019
DOI: 10.1002/acn3.50868
|View full text |Cite
|
Sign up to set email alerts
|

Variants in MME are associated with autosomal‐recessive distal hereditary motor neuropathy

Abstract: Objective To identify a new genetic cause in patients segregating distal hereditary motor neuropathy (dHMN) with an autosomal recessive pattern. Methods Whole‐exome sequencing was conducted in two siblings and was combined with segregation analysis. Additionally, 83 unrelated dHMN patients with unknown genetic cause were screened. RNA analysis was performed using blood lymphocytes and HEK293 cells transfected with mutant plasmids. Immunohistochemistry and Western blot analysis was applied to the nerve tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Although the majority of dHMN patients showed an autosomal dominant inherited mode, autosomal recessive dHMNs have been associated with variants in the SORD , IGHMBP2, PLEKHG5, DNAJB2, SIGMAR1, SYT2, ATM, TBCE , and VRK1 genes 20,32 . Our study indicated that variants in the MME gene were associated with autosomal‐recessive dHMN, and as the second disease‐causing gene for genetically confirmed cases in our patient cohort.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although the majority of dHMN patients showed an autosomal dominant inherited mode, autosomal recessive dHMNs have been associated with variants in the SORD , IGHMBP2, PLEKHG5, DNAJB2, SIGMAR1, SYT2, ATM, TBCE , and VRK1 genes 20,32 . Our study indicated that variants in the MME gene were associated with autosomal‐recessive dHMN, and as the second disease‐causing gene for genetically confirmed cases in our patient cohort.…”
Section: Discussionmentioning
confidence: 52%
“…Two unrelated individuals presented with gait disturbance and length‐dependent motor neuropathy, and had a loss‐of‐function biallelic variant (c.757delG, p.A253Qfs*27) in the SORD (NM_003104) gene. 19 Four dHMN patients from three families were associated with loss‐of‐function variants in the MME (NM_000902) gene, of which three patients have been described in our previous report, 20 and the last showed chronic progressive weakness and wasting of distal limbs. A novel c.3854A>C (p.K1285T) variant in the ATP7A (NM_000052) gene was associated with early‐onset dHMN patient with initial involvement of upper limb.…”
Section: Resultsmentioning
confidence: 96%
“…However, in three cases, disease onset was before age 35 years. Moreover, we ascertained five patients with predominant motor involvement or pyramidal tract signs, leading to a diagnosis of dHMN in one family (similar to previously reported cases 43 ) and ALS in three families.…”
Section: A C C E P T E Dmentioning
confidence: 70%
“…Interestingly, two homozygous mutations c.1342C>T (p.Arg448*) and c.1861T>C (p.Cys621Arg) detected in MME were associated to CMT2 in two unrelated Iranian families, both of which were predicted to be pathogenic based on in silico analysis. Interestingly, p.Arg448* was also detected in homozygous status in Spanish patients diagnosed with late‐onset axonal CMT (Lupo et al, 2018 ) and in compound heterozygote in Chinese patients with distal hereditary motor neuropathy (Hong et al, 2019 ). While in the study by Auer‐Grumbach et al ( 2016 ) this mutation was associated with late‐onset autosomal dominant polyneuropathies.…”
Section: Discussionmentioning
confidence: 97%
“…The genetic causes of more than 90% of CMT cases are due to mutations in four genes including PMP22 , GJB1 , MFN2 , and MPZ (Auer‐Grumbach et al, 2003 ; Chung, 2006 ; Nave et al, 2007 ; Timmerman et al, 2014 ), with PMP22 mutations alone accounting for ~70% of CMT1 cases while in CMT2, mutations in GJB1 and MFN2 are more frequent (Azzedine et al, 2012 ). The MME gene (OMIM #120520) is among frequently mutated genes in patients with late‐onset axonal form of CMT (Auer‐Grumbach et al, 2016 ; Higuchi et al, 2016 ; Hong et al, 2019 ; Lupo et al, 2018 ; Senderek et al, 2020 ; Taghizadeh et al, 2020 ). MME mutations have been shown to associate to both dominant and recessive CMT2.…”
Section: Introductionmentioning
confidence: 99%